RADT-08. DOSIMETRIC FEASIBILITY OF DIRECT POST-OPERATIVE MRI-LINAC-BASED STEREOTACTIC RADIOSURGERY FOR RESECTION CAVITIES OF BRAIN METASTASES. (14th November 2022) - Sierts, M; Seravalli, E; Brand, E; Maspero, M; David, S; Philippens, M E P; Voormolen, E H J; Verhoeff, J J C
Abstract: Background: Post-operative stereotactic radiosurgery (SRS) of patients with brain metastases with single resection cavities is typically planned on a post-recovery MRI, 4-6 weeks after resection. However, meanwhile the intracranial metastasis may (re-)grow, and postponing adjuvant systemic treatment increases chance on extracranial progression as well. Anticipating direct post-operative SRS to minimize this interval would enable rapid start of systemic therapy. In this study, we considered treatment with MRI-Linac (MRL) SRS, because of the possibility to execute the post-operative MRI and SRS treatment combined on the MRL instead of on two separate systems, improving logistics and increasing patient comfort. However, it is unclear whether MRL-based SRS may be feasible from a dosimetric perspective. This study aims to shed light on the dosimetric feasibility of MRL-based SRS. METHODS: We simulated MRL treatments including thirteen patients with resectable single brain metastases treated with single fraction CT-Linac (CTL) SRS. We therefore contoured direct post-operative gross tumor volumes (GTV) and compared them to post-recovery MRI GTV. Next, we compared a non-coplanar VMAT technique for CTL (ncVMAT) to a coplanar IMRT technique for MRL (cIMRT), creating three plans per patient: a ncVMAT plan and a cIMRT plan for the direct post-operative GTV, and a post-recovery ncVMAT plan as current clinical standard. RESULTSCompared to GTVs defined on direct post-operative MRI, on post-recovery MRI 15.5% of cavities shrunk by > 2cc, and 46% expanded by > 2cc. Although direct post-operative ncVMAT plans had lower median gradient index and higher median V3Gy of the skin, they were clinically acceptable according to clinical guidelines. CONCLUSION: Although slightly inferior to non-coplanar CTL plans, direct post-operative MRL-based SRS for resection cavities of brain metastases is dosimetrically acceptable, at the trade-off between increased patient comfort and logistics. Additionally, MRL-based SRS enables substantially earlier start with adjuvant systemic therapies, thereby maximizing tumor control.